Narratives of fear and safety (Tampere University Press, 2021)
"The essays in this edited volume, written in English and French, tackle the intriguing problems of fear and safety by analysing their various meanings and manifestations in literature and other narrative media. The articles bring forth new, cross-cultural interpretations on fear and safety through examining what kinds of genre-specific means of world-making narratives use to express these two affectivities. The articles also show how important it is to study these themes in order to understand challenges in times of global threats, such as the climate crisis, and – to imagine a better future.